1989
DOI: 10.1017/s0950268800029848
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical patterns and predictability in infection

Abstract: Many infections, especially viral infections, show a certain periodicity which can be wholly or partly predictable. It is important to be able to recognize these patterns because anticipating changes in incidence should lead to better diagnosis, treatment and control of infection. In this review patterns of some viral and other infections in England and Wales which have been observed from laboratory reports over a period of 21 years, from 1967 to 1987, are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…It will permit long‐term surveillance of incidence and has facilitated a retrospective study of the effectiveness of a chickenpox vaccine on the incidence of the disease. In the post‐SARS era, study of the cyclical patterns of viral infection 21,22 and the climatic factors that influence virulence will be important to understand how to control and eradicate these diseases. Further investigation and analysis to determine the actual significance of each of the individual risk factors 23 will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…It will permit long‐term surveillance of incidence and has facilitated a retrospective study of the effectiveness of a chickenpox vaccine on the incidence of the disease. In the post‐SARS era, study of the cyclical patterns of viral infection 21,22 and the climatic factors that influence virulence will be important to understand how to control and eradicate these diseases. Further investigation and analysis to determine the actual significance of each of the individual risk factors 23 will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…RSV infected cells bind greater numbers of Neisseria meningitidis and type b Haemophilus influenzae compared with uninfected cells [25]. As RSV infects almost half of all infants by the age of 12 months and is most prevalent in the winter months [26] Table 1. The bacteria were grown on nutrient agar or for some experiments on blood agar to examine the effect of medium on binding to epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably respiratory syncytial virus (RSV) and Bordetella pertussis have a role in causing LRI in these elder patients [7]. Noah found that in England and Wales RSV and parainfluenza 1 and 2 display marked wintertime excess [8]. The most common explanation for the seasonality of respiratory infections is that human congregate indoors in the winter, thus increase the chance for contagion [1].…”
Section: Discussionmentioning
confidence: 99%